Effective Distance between Aortic Valve and Conduction System Is an Independent Predictor of Persistent Left Bundle Branch Block during Transcatheter Aortic Valve Implantation - Thomas T. Poels; Robert Stassen; Suzanne Kats; Leo Veenstra; Vincent van Ommen; Bastiaan Kietselaer; Patrick Houthuizen; Jos G. Maessen; Frits W. Prinzen (Medicina, 2021)
Background and objectives: Persistent left bundle branch block (P-LBBB) has been associated with poor clinical outcomes of transcatheter aortic valve implantation (TAVI) procedures. We hypothesized that the distance from the aortic valve to the proximal conduction system, expressed as the effective distance between the aortic valve and conduction system (EDACS), can predict the occurrence of P-LBBB in patients undergoing a TAVI procedure. Materials and methods: In a retrospective study, data from 269 patients were analyzed. EDACS was determined using two longitudinal CT sections. Results: Sixty-four of the patients developed P-LBBB. EDACS ranged between −3 and +18 mm. EDACS was significantly smaller in P-LBBB than in non-P-LBBB patients (4.6 (2.2–7.1) vs. 8.0 (5.8–10.2) mm, median values (interquartile range); p < 0.05). Receiver operating characteristic analysis showed an area under the curve of 0.78 for predicting P-LBBB based on EDACS. In patients with EDACS of ≤3 mm and >10 mm, the chance of developing P-LBBB was ≥50% and <10%, respectively. Conclusions: A small EDACS increases the risk for the development of P-LBBB during TAVI by a factor of >25. As EDACS can be measured pre-procedurally, it may be a valuable additional factor to weigh the risks of transcatheter and surgical aortic valve replacement.